Use of Cyclosporine in Uterine Transplantation - Srdjan Saso; Karl Logan; Yazan Abdallah; Louay S. Louis; Sadaf Ghaem-Maghami; J. Richard Smith; Giuseppe Del Priore (Journal of Transplantation)
Uterine transplantation has been proposed as a possible solution to absolute uterine factor infertility untreatable by any other option. Since the first human attempt in 2000, various teams have tried to clarify which immunosuppressant would be most suitable for protecting the allogeneic uterine graft while posing a minimal risk to the fetus. Cyclosporine A (CsA) is an immunosuppressant widely used by transplant recipients. It is currently being tested as a potential immunosuppressant to be used during UTn. Its effect on the mother and fetus and its influence upon the graft during pregnancy have been of major concern. We review the role of CsA in UTn and its effect on pregnant transplant recipients and their offspring.